Waldenström Macroglobulinemia: Clinical and Immunological Aspects, Natural History, Cell of Origin, and Emerging Mouse Models. (9th September 2013) - Janz, Siegfried
Abstract : Waldenström macroglobulinemia (WM) is a rare and currently incurable neoplasm of IgM-expressing B-lymphocytes that is characterized by the occurrence of a monoclonal IgM (mIgM) paraprotein in blood serum and the infiltration of the hematopoietic bone marrow with malignant lymphoplasmacytic cells. The symptoms of patients with WM can be attributed to the extent and tissue sites of tumor cell infiltration and the magnitude and immunological specificity of the paraprotein. WM presents fascinating clues on neoplastic B-cell development, including the recent discovery of a specific gain-of-function mutation in the MYD88 adapter protein. This not only provides an intriguing link to new findings that natural effector IgM + IgD + memory B-cells are dependent on MYD88 signaling, but also supports the hypothesis that WM derives from primitive, innate-like B-cells, such as marginal zone and B1 B-cells. Following a brief review of the clinical aspects and natural history of WM, this review discusses the thorny issue of WM's cell of origin in greater depth. Also included are emerging, genetically engineered mouse models of human WM that may enhance our understanding of the biologic and genetic underpinnings of the disease and facilitate the design and testing of new approaches to treat and prevent WM more effectively.